American Foreign Policy in a New Era - JERVIS, Robert (Routledge, 2005)
To say that the world changed drastically on 9/11 has become a truism and even a clichÃ©. But the incontestable fact is that a new era for both the world and US foreign policy began on that infamous day and the ramifications for international politics have been monumental.